FGF2 and EGF for the Regeneration of Tympanic Membrane: A Systematic Review - Zhengcai Lou; Zihan Lou; Yumeng Jiang; Zhengnong Chen (Stem Cells International)
Objective. A systematic review was conducted to compare the effectiveness and safety of fibroblast growth factor-2 (FGF2) and epidermal growth factor (EGF) for regeneration of the tympanic membrane (TM). Methods. The PubMed database was searched for relevant studies. Experimental and clinical studies reporting acute and chronic TM perforations in relation to two healing outcomes (success rate and closure time) and complications were selected. Results. A total of 47 studies were included. Five experimental studies showed closure rates of 55%–100% with FGF2 compared with 10%–62.5% in controls for acute perforations. Five experimental studies showed closure rates of 30.3%–100% with EGF and 3.6%–41% in controls for chronic perforations. Two experimental studies showed closure rates of 31.6% or 85.7% with FGF2 and 15.8% or 100% with EGF. Nine clinical studies of acute large perforations showed closure rates of 91.4%–100% with FGF2 or EGF. Two clinical studies showed similar closure rates between groups treated with FGF2 and EGF. Seven clinical studies showed closure rates of 88.9%–100% within 3 months and 58%–66% within 12 months using FGF2 in repair of chronic perforations, but only one study showed a significantly higher closure rate in the saline group compared with the FGF2 group (71.4% vs. 57.5%, respectively, P=0.547). In addition, three experimental studies showed no ototoxicity associated with FGF2 or EGF. No middle ear cholesteatoma or epithelial pearls were reported, except in one experimental study and one clinical study, respectively. Conclusions. FGF2 and EGF showed good effects and reliable safety for the regeneration of TM. In addition, EGF was better for the regeneration of acute perforations, while FGF2 combined with biological scaffolds was superior to EGF for chronic perforations, but was associated with high rates of reperforation over time. Further studies are required to determine whether EGF or FGF2 is better for TM regeneration.